Analysis of The Effect Of Sharia Financial Technology (Fintech) on Increasing Literacy and Inclusion of Sharia Financial Inclusion of Msmes in Dki Jakarta - Widiawati, Widiawati; Ani Nuraini, Ani Nuraini; Arif Haryana, Arif Haryana (Journal of Entrepreneur and Business, 2023)
The purpose of this study is to analyze the effect of Islamic fintech Digital Payment System services on increasing MSME Islamic financial literacy and inclusion in DKI Jakarta. This research method is quantitative research with smartPLS analysis tool. The population in this study is MSMEs in DKI Jakarta. Sampling technique using purposive sampling technique, which amounted to 100 samples of MSMEs. Data collection techniques using a questionnaire. The results showed that the Digital Payment System variable had a t-statistic effect on Financial Literacy of 4.174. The Digital Payment System variable has a t-statistical effect on Financial Inclusion of 4,345. The Digital Payment System variable has a t-statistical effect on Financial Inclusion through Financial Literacy of 2.075. Financial Literacy variable has a t-statistic effect on Financial Inclusion of 3,103. The conclusion of this study is that the fintech digital payment system has a positive and significant effect on MSME sharia financial literacy and inclusion in DKI Jakarta, both direct, indirect and total effects. Suggestions for financial institutions are expected to improve Islamic Fintech financial services. MSMEs are expected to improve their capabilities and skills in digitizing financial services. For further researchers, other research can be carried out with a wider scope of research objects and variables. Suggestions for financial institutions are expected to improve Islamic Fintech financial services. MSMEs are expected to improve their capabilities and skills in digitizing financial services. For further researchers, other research can be carried out with a wider scope of research objects and variables. Suggestions for financial institutions are expected to improve Islamic Fintech financial services. MSMEs are expected to improve their capabilities and skills in digitizing financial services. For further researchers, other research can be carried out with a wider scope of research objects and variables. Keywords: Financial Technology, Digital Payment System, Islamic Financial Literacy, Islamic Financial Inclusion